1995
DOI: 10.1007/bf02102889
|View full text |Cite
|
Sign up to set email alerts
|

Say it once again: Effects of repeated questions on children's event recall

Abstract: In this paper, we review research examining the influences of repeated questioning on children's event recall. Issues addressed include how children's free recall changes across multiple recounts of the same event, whether responding to specific questions about an event affects subsequent responses to those same questions, and whether there are developmental differences in how children respond to repeated questioning. Both naturalistic studies of conversational remembering and more controlled studies using sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
1
41
0
Order By: Relevance
“…When the families were visited at each successive interview, they were asked about how much the target events had been discussed since our last visit, and on all those after 6 months had passed the parents claimed that the events either had not been talked about at all or there had occasionally been only brief allusions to them since the events were 'old news'. Similar patterns of event discussion have been found by others (e.g., Fivush & Schwarzmueller, 1995).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…When the families were visited at each successive interview, they were asked about how much the target events had been discussed since our last visit, and on all those after 6 months had passed the parents claimed that the events either had not been talked about at all or there had occasionally been only brief allusions to them since the events were 'old news'. Similar patterns of event discussion have been found by others (e.g., Fivush & Schwarzmueller, 1995).…”
supporting
confidence: 73%
“…This is not to say that the only reason the injury event was so well-remembered is that it was highly discussed, or in other words, that it would not have been well-remembered if not for family discussion. For salient real-life events, some researchers have found that recall amount and accuracy were not related to how frequently the events were talked about, according to parental reports (Fivush et al, 2004;Fivush & Schwarzmueller, 1995). Larkina and Bauer (2012) experimentally manipulated the amount of parent-child talk about target events by instructing parents to treat some randomly selected events as 'family stories' and talk about them with their 4-year-olds at least monthly for a year, while other selected events were seldom discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Turning ®rst to investigations of consistency, some recent reviews have appeared (Fivush et al, in press;Fivush and Schwarzmueller, 1995;Poole and White, 1995). The type of interview seems to have important effects.…”
mentioning
confidence: 99%
“…Instead, questions differed considerably across interviews. As well, children are sensitive to the listener's state of knowledge and often do not repeat information the listener already knows (Fivush and Schwarzmueller, 1995;Menig-Peterson, 1975). Since many of the repeated interviews in the above studies were conducted by interviewers familiar with the events being recounted, this may have negatively affected consistency.…”
mentioning
confidence: 99%
See 1 more Smart Citation